Distribution of sediment ammonia-oxidizing microorganisms in plateau freshwater lakes - Yong Liu; Zhang, Jingxu; Zhao, Lei; Li, Yuzhao; Dai, Yu; Xie, Shuguang (APPLIED MICROBIOLOGY AND BIOTECHNOLOGY, 2015)
Both ammonia-oxidizing bacteria (AOB) and archaea (AOA) can play important roles in ammonia biotransformation in ecosystems. However, the factors regulating the distribution of these microorganisms in lacustrine ecosystems remain essentially unclear. The present study investigated the effects of geographic location on the distribution of sediment AOA and AOB in 13 freshwater lakes on the Yunnan Plateau (China). The spatial dissimilarity in the abundance and structure of sediment AOA and AOB communities was observed in these plateau lakes. AOA abundance was usually less than AOB abundance, and the AOA/AOB ratio was positively correlated with water depth. Nitrososphaera-like AOA occurred in most of the studied lakes and were dominant in two lakes. Nitrosospira was the dominant AOB species in most of the lakes, while Nitrosomonas showed high abundance only in three lakes. In addition, geographic location was found to affect lake sediment AOB community structure.